2020
DOI: 10.1088/1757-899x/918/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of transport and logistics processes in agriculture

Abstract: This article discusses the optimization of transport and logistics processes in an agricultural enterprise. The use of new engineering support will allow the company to significantly reduce its costs and energy resources. The recommendations received are quite relevant and justified, and will find appropriate application in the production and economic activities of an enterprise of a certain industry affiliation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Road and information constructions have resulted in the efficiency of rural and urban-rural trade, connected rural and urban areas, and mobilized circulation of agricultural products [23,24]. At the same time, with the process of agricultural modernization, scientific production technology, and the application of modern science and technology to optimize the layout of agricultural enterprises and logistics processes [25], when agricultural conditions reach a certain level, they cause processing and manufacturing enterprises and e-commerce logistics enterprises to assemble, realize the scale of the industrial economy, and improve the competitiveness of rural e-commerce logistics and modern agriculture. From the above research literature, it can be concluded that agricultural modernization has an important role in promoting the development of the rural e-commerce logistics industry and the transformation of agricultural production models.…”
Section: The Relationship Between Rural E-commerce Logistics and Agri...mentioning
confidence: 99%
“…Road and information constructions have resulted in the efficiency of rural and urban-rural trade, connected rural and urban areas, and mobilized circulation of agricultural products [23,24]. At the same time, with the process of agricultural modernization, scientific production technology, and the application of modern science and technology to optimize the layout of agricultural enterprises and logistics processes [25], when agricultural conditions reach a certain level, they cause processing and manufacturing enterprises and e-commerce logistics enterprises to assemble, realize the scale of the industrial economy, and improve the competitiveness of rural e-commerce logistics and modern agriculture. From the above research literature, it can be concluded that agricultural modernization has an important role in promoting the development of the rural e-commerce logistics industry and the transformation of agricultural production models.…”
Section: The Relationship Between Rural E-commerce Logistics and Agri...mentioning
confidence: 99%
“…Extensive use of a significant part of the territory has created the problem of ordering the territory with the maximum possible improvement of the habitat. It is necessary to reboot the areas of extensive residential development in the direction of a reasonable increase development of the territory [2]. The modern development of the territory of the Chelyabinsk region is greatly distorted by the presence of large environmentally dirty metallurgical enterprises in the city.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the Southern Urals found itself in a difficult situation, due to illconceived, and sometimes barbaric human economic activity. One of the urgent problems of the Chelyabinsk region for several decades has been the metallurgy industry, mechanical engineering, electric power industry, utilization and processing of various types of waste [2]. The ecology of the natural environment in the Chelyabinsk region is considered to be the most unfavorable among the regions of Russia.…”
Section: Introductionmentioning
confidence: 99%